The Composition and Tradition of Erimḫuš - Boddy, Kaira, (Cuneiform Monographs ;, 2021)
With The Composition and Tradition of Erimḫuš Kaira Boddy offers the first comprehensive study of the lexical list Erimḫuš. Boddy gives a detailed analysis of its structure and the ways in which the text and its role in scribal scholarship changed over time. Erimḫuš was highly valued by the Assyrian and Babylonian scholars of the first millennium BCE and several centuries earlier even caught the interest of the Hittites, who had their own ingenious ways of interpreting and using the material. Originally a bilingual list collecting groups of Akkadian words and their Sumerian equivalents, Erimḫuš took on a radically different character in Ḫattuša.